DAILY—A Personalized Circadian Zeitgeber Therapy as an Adjunctive Treatment for Alcohol Use Disorder Patients: Study Protocol for a Randomized Controlled Trial - Hühne, Anisja; Hoch, Eva; Landgraf, Dominic (Frontiers in Psychiatry, 2021)
Background Hallmarks of alcohol use disorder (AUD) are disturbances of circadian rhythms and everyday structures. While circadian rhythms dictate the timing of daily recurring activities such as sleep, activity, and meals, conversely, these activities represent time cues, so called Zeitgebers, that the circadian system uses to synchronize with the environment. Here we present a study protocol for our newly developed therapy approach for AUD patients, in which we take advantage of this mutual influence and stabilize and strengthen their circadian system by creating strict daily schedules for daily Zeitgeber activities. Since every person has a circadian system with its own characteristics and is subject to social obligations, the daily plans are personalized for each test person. Our hypothesis is that a regular exposure to Zeitgebers stabilizes behavioral and physiological circadian rhythms and thereby reduces the risk of alcohol relapses and depressive symptoms and facilitates physical recovery in AUD patients during the first weeks of their addiction therapy. Methods/Design The study is a six-week single site trial with a controlled, randomized, single-blinded, parallel-group design including patients with a diagnosis of AUD. The study runs parallel to the standard addiction therapy of the clinic. Patients are randomly assigned to either an intervention group (DAILY) or a sham control group (placebo treatment). Questionnaires and physiological assessments of both groups are conducted before and immediately after the intervention or control treatment. According to our hypothesis, the primary outcomes of this study are improvements of regularity, alcohol consumption, and relapse rate in AUD patients compared to AUD patients receiving control treatment. Secondary outcomes are reduced depressive symptoms and increased physical recovery. Discussion This study is a randomized controlled trial to investigate the efficacy of a personalized circadian Zeitgeber therapy as an adjunctive treatment for alcohol use disorder patients. The overall goal of this and more extended future studies is the development of an adjunctive therapy for AUD patients that is uncomplicated in its use and easy to implement in the clinical and everyday routine. Trial registration This study is registered at the German Clinical Trial Register with the trial number DRKS00019093 on November 28, 2019.